PENGARUH GAYA KEPEMIMPINAN CAMAT TERHADAP KINERJA PEGAWAI KANTOR KECAMATAN ANGGAREJA KABUPATEN ENREKANG - Erwin Erwin (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2018)
The research conducted at the district office Anggeraja with the aim of wich is to determine the effect of leadership style camat the performance of employees at the district office Anggeraja Enrekang and the factors that effect performance. This study bused quantitative descriptive research by presenting a depiction of a situation or a social phenomenon in detail. This type of research is the survey fieldwork to collect data information from respondents through questionnaires as data collection directly at the sites. In this study which is the independent variable (x) is the leadership style, while the dependent variable is the performance of employees. The sample is determined as many as 30 people. Data collection techniques are the steps most strategicof observation, interviews, questionnaires, and literature study. The results showed that : 1) the effect of leadership style on the employee performance at the district office Anggeraja Enrekang, which is very influential in the category with a score of 3,31 and the percentage is 81, 67%, and 2) factors that effect the performance of employees, namely : a) the ability to be on a score of 3,47 (86,67%) or a category of higly influential, and b) the motivation is at a score of 3,57 (89,17%) or very influential category.